3D High-Spatial-Resolution Cerebral MR Venography at 3T: A Contrast-Dose-Reduction Study - Tomasian, A.; Salamon, N.; Krishnam, M.S.; Finn, J.P.; Villablanca, J.P. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: The effect of various contrast-dose regimens for cerebral MR venography (MRV) has not been previously evaluated at 3T, to our knowledge. Our purpose was to evaluate and compare the diagnostic image quality resulting from half-versus-full-dose contrast regimens for high-spatial-resolution 3D cerebral MRV at 3T.MATERIALS AND METHODS: Forty consecutive patients with known or suggested cerebrovascular disease underwent 3D high-spatial-resolution (0.7 exttimes 0.6 exttimes 0.9 mm3) cerebral contrast-enhanced MRV (CE-MRV) at 3T, by using an identical acquisition protocol. Patients were assigned to 1 of 2 groups: 1) full-dose (~0.1 mmol/kg), and 2) half-dose (~0.05 mmol/kg). Two readers evaluated the resulting images for overall image quality, venous structure definition, and arterial contamination. Signal intensity–to-noise-ratio (SNR) and contrast-to-noise-ratio (CNR) were evaluated in 8 consistent sites. Statistical analysis was performed by using Mann-Whitney U, Wilcoxon signed rank, and t tests and a κ coefficient.RESULTS: Both readers scored venous-structure definition as excellent or sufficient for diagnosis in approximately 90% of segments for the full-dose group (κ = 0.87) and in approximately 80% of segments for the half-dose group (κ = 0.85). Delineation grades were significantly lower for small venous segments, including the middle cerebral, septal, superior cerebellar, inferior vermian, posterior tonsillar, and thalamostriate veins in the half-dose group (P < .01). No significant difference existed for arterial contamination grades between the 2 groups (P > .05). SNR and CNR values were lower in the half-dose group (P < .01).CONCLUSIONS: At 3T, high-spatial-resolution cerebral MRV can be performed with contrast doses as low as 7.5 mL, without compromising image quality as compared with full-dose protocols, except in the smallest veins, and without compromise of acquisition speed or spatial resolution.